2021
DOI: 10.3389/fphar.2021.713178
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of Single Nucleotide Variant Assays for Human Leukocyte Antigen Haplotypes HLA-B*15:02 and HLA-A*31:01 Across Diverse Ancestral Backgrounds

Abstract: The human leukocyte antigen haplotypes HLA-B*15:02 and HLA-A*31:01 have been linked to life-threatening adverse drug reactions to the anticonvulsants carbamazepine and oxcarbazepine. Identification of these haplotypes via pharmacogenetic techniques facilitates implementation of precision medicine to prevent such reactions. Using reference samples from diverse ancestral origins, we investigated the test analytical validity (i.e., ability to detect whether or not the haplotypes were present or absent) of TaqMan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…In 1 KG_AMR, specificity was nearly complete (0.96) for rs1061235, and somewhat lower for rs17179220 (0.86), whereas PPV ranged between 0.42 (rs17179220) and 0.70 (rs1061235). All false positives for rs1061235 were due to the presence of this SNV in the HLA-A*33:01 haplotype, as previously reported for other populations ( Amstutz et al, 2013 ; He et al, 2015 ; Buchner et al, 2021 ). False positives for rs17179220, however, were not linked to HLA-A*33:01.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In 1 KG_AMR, specificity was nearly complete (0.96) for rs1061235, and somewhat lower for rs17179220 (0.86), whereas PPV ranged between 0.42 (rs17179220) and 0.70 (rs1061235). All false positives for rs1061235 were due to the presence of this SNV in the HLA-A*33:01 haplotype, as previously reported for other populations ( Amstutz et al, 2013 ; He et al, 2015 ; Buchner et al, 2021 ). False positives for rs17179220, however, were not linked to HLA-A*33:01.…”
Section: Resultssupporting
confidence: 79%
“…Two SNVs, namely rs1061235 (GRCh38.p13 chr 6, NC_000006.12:g.29945521A>T) and rs17179220 (GRCh38.p13 chr 6, NC_000006.12:g.29853458G>A) have been proposed for tagging the HLA-A*31:01 haplotype: de Bakker et al (2006) first reported complete linkage disequilibrium (LD) between rs1061235 and HLA-A*31:01 in the HapMap European (CEU) sample. Subsequent work revealed that rs1061235 is also linked to HLA-A*33 haplotypes, which impacts the predictive performance of rs1061235 to identify carriers of HLA-A*31:01 ( Amstutz et al, 2013 ; Thorstensen et al, 2014 ; Buchner et al, 2021 ). High LD of rs17179220 with HLA-A*31:01 was initially detected in Han Chinese ( Zhou et al, 2016 ), and subsequently verified in a large set of ancestrally diverse populations ( Erlichster et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%